The Prospects of Reading Circles for Fostering EFL Learners’ Motivation to Read and Engagement - Khonamri, Fatemeh; Azizi, Neshat; Akimjak, Amantius; Kurilenko, Viktoria (Journal of Education Culture and Society, 2024)
Thesis. This study explores three important concepts in the field of language teaching. The purpose is to investigate whether reading circles are effective means of improving students’ reading motivation and engagement. Concept. To this end, using a qualitative design, 27 students of English language and literature from the University of Mazandaran participated in the study. The data were collected through a learning journal, teacher’s field notes and a subsequent semi-structured interview. All the students were engaged in a reading circle once a week for the duration of 12 weeks. Analysis of the data was done based on coding and content analysis. Results and Conclusion. Results indicated that reading circles had the potential to motivate learners to read more and also was an appealing activity for them to engage in and contribute to their circles. The findings suggested that the unrepeatable configuration of the group and the goal setting mindset promoted by the activity and a high sense of achievement and enjoyment after completion of the task corresponded positively with their high level of engagement and motivation to read new passages. Even though the results cannot be generalised to other contexts, they can be suggested to be applied in other EFL contexts for motivating learners to engage more in reading.